Mismanagement of Drug Supply (Case Study at Gunungsitoli Nias Hospital in 2018) - Eltria Andriyani Syafitri (Akupun Tour Publisher, 2023)
Purpose: The research was conducted to determine the miss management of the supply of pharmaceutical drugs in Gunungsitoli Nias Hospital. Method: This research is a type of case study qualitative research. The informants from this study were the head of the pharmaceutical warehouse, the pharmacy warehouse officer and the head of the Farmasai Installation as the validity of the data. Data collection techniques in research use observation and in-depth interviews. Results: The results of this study found that the process of managing drug supplies in Gunungsitoli Regional Public Hospital was due to problems due to frequent out of stock of drugs caused by delays in delivery from providers, increased use of drugs by doctors to patients, changes in occupation by doctors, empty medicine needed in the market and location distant geographical. The stock of drugs that are often erratic is caused by several causes, one of them is the length of time the items ordered and the empty drugs needed on the market are empty. Disscusion and Conclusion: Conclusions from the results of interviews obtained from informants that if the stock of drugs in the hospital is exhausted, the hospital will offer drugs with the same class, effects and content almost the same but the name is different to the patient. Based on observations by researchers, most pharmacists offer patients without contacting a doctor. If this continues to eat it will have a hazard for patients, doctors and hospitals.